Successfully transitioning systems and minds: The impact of change management and organizational culture on readiness for organizational change - Celestial, Jane Lyra M. (Animo Repository, 2023)
Family businesses take up most of the Philippine economy. However, one of the major struggles of family-owned small-to-medium enterprises (SMEs) is their ability and preparedness for change. Readiness for organizational change (ROC) is a key contributor in the successful implementation of change. To test the existing theories, the researchers aim to answer, “How does organizational culture and change management affect readiness for organizational change?”. Yin’s (1994) single-embedded case study, using a combination of surveys and interviews for data collection, was used to test the following propositions: P1: Employing the use of change management (CM) improves the readiness for organizational change (ROC) of Baguio Country Mart, P2:Organizational culture (OC) plays an important role in Baguio Country Mart’s level of readiness for organizational change (ROC) and P3: Improving Baguio Country Mart’s organizational culture (OC) practices enhances the influence of change management (CM) to the readiness for organizational change (ROC) . The chosen subject of the study is Baguio Country Mart, a small retail business based in Baguio, Philippines wherein a total of thirty seven (37) employees and two (2) owners were surveyed. The results revealed a positive and significant relationship between independent variables, CM and OC, and dependent variable, ROC. Furthermore, the use of either CM or OC increases an organization's ROC, but simultaneously employing both is a more effective means to increasing ROC. The case study also provides recommendations to Baguio Country Mart for each of the three variables so these aspects in their operations may be further enhanced and allows them to be more readily equipped for coming changes. Keywords: Change, Change Management, Organizational Culture, Readiness for Organizational Change, SME